Design and Optimization of FTTH Architecture - Derahman, Mohd Noor (2002)
Recently, the growth of Internet and uses of digital contents have significantly increased the demand for high-speed access network. Similar cases are also seen for the use of intranet and extranet services. The limitation of current access network such as the asymmetric digital subscriber line (ADSL) in terms of low bit rate and short of coverage span resulted in the exploration on fibre access scenario. Fibre-tothe- home (FTTH) brings the broadband access network capabilities directly to the customer premises with high splitting ratio and wide fibre span. It is seen as the linchpin technology to enable the future applications such as voice, video and data run, satisfying the ever-increasing need for bandwidth. This thesis shows the study of FTTH access network based on passive optical network (PON). The two types of FTTH; A-PON and Super-PON have been studied thoroughly to optimize their architecture to help network engineers in designing the system. The cost analysis is also carried out. The simulation is done using OptSim 3.0 and the result is verified with the experiment in the laboratory. It is found that the optimum configuration of a A-PON FTTH access systems with the bit rate of 2Gb/s with the use of 32 branching number is at the distance of 20 km. The power enhancement offered by Erbium-doped Fibre Amplifier (EDFA) provides for large distribution branches (thus the subscribers) and the length of fibre span can be extended up to 100 km.